Identity Crisis in Randa Abdel-Fattah’s Ten Things I Hate about Me (2006) - Haider Hussein Katea, H. K. Abd al Janabi, Th. Rashid. Shayyal. Az-Zubaidy, (Opción, 2020)
The critical objective of this research paper is to identify the range of identities that the human being is made to possess in the contemporary era. In this paper, we focus on Randa Abdel-Fattah‟s novel entitled Ten Things I Hate About Me order to demonstrate the multiple character of identity as a concept, particularly in the context of diasporic communities like Palestinian refugees. Therefore, it can be a call for a deeper understanding of the multifaceted character of identity, the complexity of the human, and also the tragedy of large sections of humanity.